Seminar "Create A Great Leader and Master Communication" As an Effort to Improve Student Communication Skills in The Digital Era - Iswadi, Iswadi; Iriansyah, Herinto Sidik; Anom, Erman (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2024)
Background: Communication is an ability that has a significant impact on students. Training for this activity must always be carried out. Contribution: The purpose of this study is to explain the impact of seminar activities to improve students' abilities and skills in conducting open and effective communication patterns in the digital era that is currently taking place. Method: The research method used in this study is descriptive qualitative. Data collection techniques carried out include observation, interviews, and documentation studies. Result: Based on data that has been collected, the seminar that has been done is known to have a positive impact and helps students have high enthusiasm to learn about effective communication and tips for maintaining communication ethics in the digital age. Conclusion:  In addition, with the material presented, students can understand the urgency of the formation of communication skills to improve the image, confidence, as well as the responsibilities they have in the future.